Evaluating a Strategy for Implementation and Sustainability of School‐Based Health Centers in 3 Disparate Communities. (28th January 2020) - Johnson, Veda; Ellis, Ruth S.; Hutcherson, Valerie
ABSTRACT: BACKGROUND: School‐based health centers (SBHCs) increase access to health care and improve academic achievement for underserved students. We report on the test of a strategy to take SBHCs to scale by addressing the issues of community need and support and financial sustainability. METHODS: Using mixed methods, we collected data on student enrollment, utilization, health outcomes, seat time, patient revenues, surveys and key informant interviews from SBHCs located in 3 geographically and demographically different communities over a 2‐year period. RESULTS: The 3 health centers were comparable in their capacity to implement their operations and achieve quality outcomes but varied considerably in their abilities to achieve sustainability after 2 years of operation. All participated in a planning phase and were able to achieve community buy in and support which impacted their implementation. Only one of the SBHCs which had the highest patient utilization was able to generate enough revenue from patient billings to become sustainable after the second year. CONCLUSION: Expanding SBHCs requires a period of planning to generate community buy in and support which is required for successful implementation. Sustainability requires sustained high clinic utilization and is enhanced by health centers that are able to receive high Medicaid reimbursements.